Herbicidal Control of Eupatorium - George, K. (Indian Forester, 1968)
In view of the necessity to evolve suitable measures of herbicidal control of the weed, Eupatorium in Forest and Plantation areas preliminary trials on herbicidal efficacies of spray application of 2,4-D and Gramaxone on this plant in the laboratory and in the field were carried out. It has been observed that Gramaxone is herbicidally more potent than 2,4-D. It is suggested that economic control of Eupatorium could be advantageously achieved by employing Gramaxone.